Pregnancy-related acute renal failure: A single-center experience - Goplani, K. R. (Medknow Publications, 2008)
Pregnancy-related acute renal failure (ARF) is a common occurrence and is associated with substantial maternal and fetal mortality. It also bears a high risk of bilateral renal cortical necrosis. We conducted this study to evaluate the contributing factors and to assess the frequency of cortical necrosis. In this prospective study, of the 772 patients with ARF admitted at our institute between January 2004 and May 2006, 70 had ARF associated with pregnancy complications. ARF was diagnosed by documenting oliguria (urine output <400 ml/d) or mounting azotemia in the presence of normal urine output. (serum creatinine >2 mg%). Renal biopsy was performed if a patient was found to be oliguric or required dialysis support at the end of three weeks. The incidence of pregnancy-related ARF was 9.06%. Approximately 20% cases occurred due to postabortal complications in early pregnancy and 80% following complications in late pregnancy. Puerperal sepsis was the most common etiological factor in 61.42% of the patients. Preeclampsia accounted for 28.57% of ARF. Two-thirds of patients recovered with dialysis and supportive care. The incidence of biopsy proven renal cortical necrosis was 14.8% (10 of the 70 patients). The incidence of renal cortical necrosis was 28.57% in the early pregnancy group and 10.71% in the late pregnancy group. Postabortal sepsis was the most common precipitating event for renal cortical necrosis. Maternal mortality was 18.57%. Sepsis accounted for a majority of deaths (61.53%). Pregnancy-related ARF is common in western India. Puerperal sepsis is the most frequent etiological factor. Renal cortical necrosis is common and postabortal sepsis was the most common precipitating event. Sepsis accounted for a majority of maternal mortality.